2013
DOI: 10.1371/journal.pone.0070501
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic Relationships and Species Delimitation in Pinus Section Trifoliae Inferrred from Plastid DNA

Abstract: Recent diversification followed by secondary contact and hybridization may explain complex patterns of intra- and interspecific morphological and genetic variation in the North American hard pines (Pinus section Trifoliae), a group of approximately 49 tree species distributed in North and Central America and the Caribbean islands. We concatenated five plastid DNA markers for an average of 3.9 individuals per putative species and assessed the suitability of the five regions as DNA bar codes for species identifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
64
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 83 publications
(72 citation statements)
references
References 79 publications
3
64
0
4
Order By: Relevance
“…The grouping seems to match with a taxonomic treatment of Farjon (2005) and some molecular phylogeny (Liston et al 1999;López et al 2002;Zhang and Li 2004;Eckert and Hall 2006;Gernandt et al 2009;Hernández-León et al 2013;Wang and Wang 2014). In this observation fluorescent band patterns of chromosomes are performed in moderate number of Pinus species.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…The grouping seems to match with a taxonomic treatment of Farjon (2005) and some molecular phylogeny (Liston et al 1999;López et al 2002;Zhang and Li 2004;Eckert and Hall 2006;Gernandt et al 2009;Hernández-León et al 2013;Wang and Wang 2014). In this observation fluorescent band patterns of chromosomes are performed in moderate number of Pinus species.…”
Section: Discussionsupporting
confidence: 80%
“…subsection Pinus by unknown structural change of chromosomes and then this karyotype may be advance and divorced recently in pine species. This speculation should be considered with taxonomic treatments (Mirov 1967;Little and Critchfield 1969;Farjon and Styles 1977;Farjon 2005) and molecular phylogeny (Price et al 1998;Liston et al 1999;López et al 2002;Zhang and Li 2004;Eckert and Hall 2006;Gernandt et al 2009;Hernández-León et al 2013;Wang and Wang 2014).…”
Section: P Yunnanensismentioning
confidence: 99%
“…Its six predicted transmembrane segments and two moderately hydrophobic stretches are conserved and are likely the functional domains, and the remaining portions are highly divergent. A protein alignment showed that all of the B. napus ycf1 variants are located in the highly divergent portions, suggesting their nonmutational functionality, which would partially explain why ycf1 has a rapid evolutionary rate (Hernández‐León et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…Further plastid DNA studies have verified the paraphyly of Pinus subsects. Attenuatae and Australes (Parks et al 2012;Hernández León et al 2013), but nuclear DNA studies are also under way to corroborate the plastid results and to more conclusively establish whether the Oocarpa group is monophyletic. At present, the Oocarpa group, or the Oocarpae, is an appealing descriptive name for the serotinous egg-cone pines (including the Leiophyllae) naturally distributed in the southwestern United States, Mexico, and Central America.…”
Section: Pinus Vallartensismentioning
confidence: 96%